A Systematic Review of the Impact of COVID-19 on Children's Outcomes - Nurhidayah, Ikeu; Mega Tamara; Dyah Setyorini (Jurnal Promkes: The Indonesian Journal of Health Promotion and Health Education, 2024)
Background: The COVID-19 pandemic has had an impact on the health of children. Nurses and healthcare professionals should know the latest information regarding the impact of Covid-19 on children. Aims: This literature review aims to identify the impact of COVID-19 on children's outcomes. Method: This literature study uses the narrative review method. CINAHL, PubMed, Proquest, Science Direct, and Google Scholar were used to conduct the literature search. The keywords used are "Children” AND "Coronavirus Disease 2019” OR "COVID-19” AND "Impact” OR "Effect”. The articles used were subjected to critical assessment. Seven quantitative research articles were reviewed in this literature study. Results: This study shows that the COVID-19 pandemic has impacted children's health and education. In terms of health, COVID-19 causes changes in physical activity to more sedentary behavior, delayed immunization, a negative impact on the mental health of children and adolescents, and children with special needs health. In the education aspect, COVID-19 has brought about a transformation in the field. Conclusion: The ongoing COVID-19 pandemic makes assessing the short- and long-term effects on children difficult. The need to conduct further research will benefit nurses and healthcare professionals in providing appropriate nursing services to children and families.